Portland cement - Bye, G. C. (Institution of Civil Engineers Publishing, 2011)
The third edition of this best selling book provides a concise overview of the properties and manufacturing processes of Portland Cement, which students of material sciences and graduates looking to enter the cement or concrete industries will find invaluable.
Keywords: Portland cement.; elektronické knihy; electronic books